Research use of electronic health records: patients' perspectives on contact by researchers. (6th July 2018) - Brelsford, Kathleen M; Spratt, Susan E; Beskow, Laura M
Abstract: Objective: The use of electronic health records (EHRs) for research has the potential to improve the diagnosis and treatment of disease, yet contact with patients based on results of EHR phenotyping has received little attention. Researchers will almost certainly discover discrepancies in EHRs that call for resolution and, in some cases, raise the ethical dilemma of whether to contact patients about a potentially undiagnosed or untreated health concern. The objective of this study was to explore patients' attitudes and opinions about potential contact by researchers who have had access to their EHRs. Materials and methods: We conducted 15 focus groups in four diverse counties in the southeastern United States. We designed vignettes to describe different situations in which researchers conducting a hypothetical study might have reason to consider contact with patients. Results: Many patients believed it was important for researchers to take action if they discovered information suggesting a current serious health concern. Relaying the information through patients' physicians was considered the most appropriate course of action. Across vignettes, there were significant differences between urban and rural sites. Discussion and conclusions: Researchers may increasingly encounter situations involving contact with patients following EHR phenotyping. They should carefully consider the possibility of such contact when planning their studies, including the time and expertise needed to adjudicate potentially serious discrepancies. Our focus group results are one source of input for the development of ethical approaches to the research use of EHRs.